2015
DOI: 10.1371/journal.pone.0123840
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated to Vaccination against Influenza among Elderly in a Large Brazilian Metropolis

Abstract: BackgroundThis study aimed to estimate coverage and identify factors associated to vaccination against influenza in the elderly population.MethodsThe study design was cross-sectional and population based. Data was collected in 2010 by the Health, Well-Being and Aging Study. Sample consisted of 1,341 community-dwelling elderly, in São Paulo, Brazil. Association between vaccination and covariates was evaluated by means of prevalence ratios estimated by Poisson regression models.ResultsSelf-reported vaccination c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 36 publications
2
47
1
5
Order By: Relevance
“…27 Regarding the factors associated with vaccine uptake, several studies have shown that it is related to individual characteristics, 4,12,25,28,29 such as gender, 13,29 socioeconomic conditions, 4,25 and general health status. 4,12,13 The adjusted analysis confirmed the importance of current life style, use of health care, and socioeconomic determinants.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…27 Regarding the factors associated with vaccine uptake, several studies have shown that it is related to individual characteristics, 4,12,25,28,29 such as gender, 13,29 socioeconomic conditions, 4,25 and general health status. 4,12,13 The adjusted analysis confirmed the importance of current life style, use of health care, and socioeconomic determinants.…”
Section: Discussionmentioning
confidence: 63%
“…The role of current lifestyle in predicting vaccine uptake has been reported earlier 4,12,18 in studies highlighting a higher prevalence of vaccination among older adults who practice physical activities and who did not smoke and drink. These associations may be explained by the fact that these individuals are more committed to healthy behaviors and have more access to health care facilities.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations